2020
DOI: 10.3390/vaccines8020263
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Influenza Vaccination on All-Cause Mortality and Hospitalization for Pneumonia in Adults and the Elderly with Diabetes: A Meta-Analysis of Observational Studies

Abstract: Diabetes is a chronic condition that can be worsened by complications such as seasonal influenza virus infections. The aim of the present meta-analysis is the systematic retrieval and analysis of all available evidence on the effects of an influenza vaccine on diabetic patients. We conducted a systematic review and meta-analysis by searching MEDLINE, Embase and the Cochrane databases from inception until April 2019. We included all types of studies reporting on the effectiveness of influenza vaccination in adu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 45 publications
1
23
0
Order By: Relevance
“…Our results highlight the major relevance of promoting seasonal influenza vaccine since immunized adults had a 40% reduction in the risk of dying (HR= 0.59, 95% CI 0.44-0.80) due to influenza pneumonia. Our overall estimate is similar to the pooled effectiveness of influenza vaccination in preventing all-cause in-hospital mortality among adults (Mantel-Haenszel Odds Ratio, MH-OR = 0.54, 95% CI 0.40-0.74) (Bechini et al 2020). The effectiveness of the seasonal influenza vaccine in reducing related morbidity and mortality has been widely proved (Dawood et al 2020).…”
Section: Discussionsupporting
confidence: 75%
“…Our results highlight the major relevance of promoting seasonal influenza vaccine since immunized adults had a 40% reduction in the risk of dying (HR= 0.59, 95% CI 0.44-0.80) due to influenza pneumonia. Our overall estimate is similar to the pooled effectiveness of influenza vaccination in preventing all-cause in-hospital mortality among adults (Mantel-Haenszel Odds Ratio, MH-OR = 0.54, 95% CI 0.40-0.74) (Bechini et al 2020). The effectiveness of the seasonal influenza vaccine in reducing related morbidity and mortality has been widely proved (Dawood et al 2020).…”
Section: Discussionsupporting
confidence: 75%
“… a The studies about the relationship between Hepatitis B virus and T2DM are not consistent . References: ( 22 , 130 , 135 143 ) . …”
Section: Methods and Inclusion Criteriamentioning
confidence: 99%
“…Dual influenza and pneumococcal vaccination of >48,000 individuals aged >60 years in China was associated with a decreased risk of hospitalization for acute respiratory illness (OR 0.49; 95% CI, 0.41-0.59) [71]. A recent meta-analysis of observational studies published up to 2019 found that, in patients with diabetes, influenza vaccination was associated with a lower mortality rate (OR 0.54, 95% CI, 0.40-0.74) [72]. The risk of hospitalization due to pneumonia was also lower among the vaccinated individuals (OR 0.89; 95% CI, 0.80-0.98) [72].…”
Section: Vaccine-preventable Diseases and Vaccination Benefitsmentioning
confidence: 99%